2018
DOI: 10.2134/jeq2018.05.0202
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Herbicides and Pesticide Mixtures in Groundwater of a Canadian Prairie Province

Abstract: Groundwater samples were collected from piezometers and water table wells in both dryland and irrigated agricultural regions of Alberta, Canada, to examine the occurrence of pesticide mixtures. Fourteen current‐use pesticides and two historical compounds were detected over a 3‐yr sampling period. Pesticide mixtures were detected in ∼3% of the groundwater samples, and the frequency of detection increased from spring (1.5%) to summer (3.8%) and fall (4.8%). Pesticide mixtures always consisted of at least one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…When 24 algal strains were analysed, the higher intracellular auxin concentrations in faster-growing strains suggested that auxin is involved in cell growth and division in microalgae (Wendy A. . Auxins are also known for their use in agriculture due to herbicide and pesticide properties (Munira et al, 2018;Quareshy et al, 2018). Cyanobacteria excrete indole acetic acid, amino acids and other growth promoting compounds into their immediate environment, which can stimulate the growth of microbial populations in soil and thereby improve crop and soil quality due to interactions with bacteria (Karthikeyan et al, 2009).…”
Section: Phytohormonesmentioning
confidence: 99%
“…When 24 algal strains were analysed, the higher intracellular auxin concentrations in faster-growing strains suggested that auxin is involved in cell growth and division in microalgae (Wendy A. . Auxins are also known for their use in agriculture due to herbicide and pesticide properties (Munira et al, 2018;Quareshy et al, 2018). Cyanobacteria excrete indole acetic acid, amino acids and other growth promoting compounds into their immediate environment, which can stimulate the growth of microbial populations in soil and thereby improve crop and soil quality due to interactions with bacteria (Karthikeyan et al, 2009).…”
Section: Phytohormonesmentioning
confidence: 99%
“…The groundwater quality could be affected by chemicals of agricultural use, and the residual pesticides and herbicides are recognized as the primary contaminants. By analyzing 436 groundwater samples in Alberta, Canada, Munira, Farenhorst, Sapkota, Nilsson, and Sheedy (2018) discovered 14 types of current‐use pesticides. Moreover, these pesticides contained at least one auxin herbicide compound, while 2,4‐D, MCPA, and clopyralid were the most frequently detected as the auxin herbicide.…”
Section: Groundwater Pollutionmentioning
confidence: 99%
“…In addition, samples collected directly from rivers tended to have fewer pesticides than effluents and tributaries, especially upstream from urban centers. Finally, most studies of pesticides in surface waters tend to be conducted beginning in early spring (May-Jun), whereas the synoptic survey was conducted in summer when pesticides such as 2,4-D and MCPA are predominantly used (Munira et al 2018) but prior to pre-harvest pesticide applications. Pesticides most 5 (1.6 ± 0.4) bd 11 (4.6 ± 0.9) cd 9 (4.0 ± 0.4) bc 10 (4.0 ± 1.3) bcde 17 (3.0 ± 0.4) C Tributary 9 (0.9 ± 0.2) ace 7 (1.7 ± 0.4) cd 3 (0.4 ± 0.3) de 5 (3.0 ± 2.0) bcde 10 (1.1 ± 0.2) B Mainstem 1 (0.2 ± 0.1) ace 2 (0.6 ± 0.1) be 2 (0.1 ± 0.1) de 2 (1.3 ± 0.2) bcde 4 (0.4 ± 0.1) A frequently detected in the synoptic survey followed a similar pattern to that reported in Anderson (2005) for the period 1995-2002, with 2,4-D, mecoprop, dicamba, and clopyralid the most frequently detected pesticides.…”
Section: Synoptic Surveymentioning
confidence: 99%
“…Pesticides can persist and be detected in surface waters outside of their application period (Kimbrough and Litke 1996). More specifically, auxin herbicides such as 2,4-D and mecoprop have been detected in soil (Anesio et al 2018), groundwater (Munira et al 2018), and stormwater (Rippy et al 2017) during the off-season, likely a consequence of their physicochemical properties and those of the soils as well as pesticide usage (quantities and formulations applied in a region). Similar results were obtained in water across the Canadian prairies (Byrtus et al 2004, Donald et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation